Efecto de la concentración de ácido ascórbico sobre la razón de aspecto y potencial Z de Nanobarras de oro crecidas por ruta química en presencia de dos surfactantes - Flores Alayo, Rider Esneyder (2017)
In the present research work, nanobarras of gold by chemical path mediated by "seeds" were synthesized, where the effect that the volume variation of a reducing agent such as ascorbic acid (AA) is generated in these, as much in its Zeta Potential, pH and Aspect Ratio. Chlorouric acid (HAuCl4) was used as precursor in the presence of a strong sodium borohydride reductant (NaBH4) and two surfactants stabilizing the CTAB / BDAC seeds at a constant molar ratio of 1.33. The volume of the weak AA reducer was varied in amounts of 80, 90, 100, 110, 120 and 130 μL. The experimental analysis was performed using UV-VIS visible ultraviolet spectroscopy, through which information on absorbance, as well as transverse and longitudinal plasmon bands were obtained. This analysis revealed that the increase of AA volume does not produce a continuous increase in the longitudinal plasmon band, but until reaching a maximum limit of 1090 nm which was for 90 μL of AA and for volume superior was observed decrease of the band of Plasmon longitudinal. In addition, the direct proportionality between longitudinal plasmon band and aspect ratio was corroborated. The analysis in a DLS (Dynamic Light Dispersion) equipment allowed to calculate the Zeta Potential of the gold nanobarras which showed to be cationic larger than +25 mV and in addition the calculation of the pH of the colloids. The analysis of results indicated that the pH of the colloid is inversely proportional to the potential Z and intensity of light absorption, where the colloid with the highest stability and lowest pH is 100 μL of AA